Impact of Pretreatment Neutrophil Count on Chemotherapy Administration and Toxicity in Dogs with Lymphoma Treated with CHOP Chemotherapy. (4th December 2017) - Fournier, Q.; Serra, J.‐C.; Handel, I.; Lawrence, J.
Abstract : Background: Prechemotherapy absolute neutrophil count (ANC) cutoffs are arbitrary and vary across institutions and clinicians. Similarly, subjective guidelines are utilized for the administration of prophylactic antibiotics in neutropenic dogs. Objectives: To evaluate the impact of various ANC cutoffs on chemotherapy administration in dogs with lymphoma treated with CHOP chemotherapy and to determine whether an association between prechemotherapy ANC and subsequent toxicity exists. The secondary objective was to evaluate a currently used ANC cutoff to indicate prescription of prophylactic antibiotics. Animals: Dogs diagnosed with lymphoma treated with CHOP chemotherapy (n = 64). Methods: Six hundred and fifteen ANCs were stratified into 6 classes. The 3 ANC cutoffs 1.5 × 10 3 /μL, 2.0 × 10 3 /μL, and 2.5 × 10 3 /μL were assessed. The presence of an association between prechemotherapy ANC class and toxicity was determined. Afebrile neutropenic dogs with ANC <1.5 × 10 3 /μL but above the criteria for prophylactic antibiotics were evaluated. Results: Chemotherapy was not administered in 7% of visits with an ANC cutoff of 1.5 × 10 3 /μL; chemotherapy would not have been administered in 10% and 16% of visits with an ANC cutoff of 2.0 × 10 3 /μL or 2.5 × 10 3 /μL, respectively. There was no association among the 3 lower prechemotherapy ANC classes and toxicity. All dogs with ANC 0.75–1.5 × 10 3 /μL recovered spontaneously without medical intervention. Conclusion and Clinical Importance: The number of dose delays was minimized with a prechemotherapy ANC cutoff of 1.5 × 10 3 /μL, and the prechemotherapy ANC class 1.5–1.99 × 10 3 /μL was not associated with an increased toxicity. Further investigation of an ANC cutoff near 0.75 × 10 3 /μL in which to prescribe prophylactic antibiotics is indicated.